Changes in Job Duration in Canada - Heisz, Andrew (Relations industrielles / Industrial Relations, 1999)
Using monthly data from the Canadian Labour Force Survey, the author investigates changes in the complete duration of new job spells from 1981 through 1996. While the average complete length of new jobs did not increase or decrease over the period, investigation of the distribution of complete job lengths reveals two important changes. First, the probability that a new job would end within 6 months rose during the 1980s, but then reversed during the 1990s, meaning that there was important change over the period as a whole. Second, the conditional probability that a job that had lasted 6 months would continue on past 5 years rose through the whole period. This pattern of change was found among virtually all demographic subgroups examined, suggesting that an economy-wide (rather than a sectoral or demographic) explanation must be sought.